Enhancing Learning Quality: Analysis of HR Management and Digital Media Utilization at TKIT Anak Sholeh Al Mubarak Pallangga Gowa - Nurmelisa; Sitti Nurbaya; Nasrullah (Income Journal Of Economics Development, 2025)
This research aims to explore how the management of human resources and the utilization of technological media contribute to enhancing the quality of learning at TKIT Anak Sholeh Al Mubarak in Pallangga, Gowa. The research employs a descriptive qualitative approach, using qualitative data derived from observation, interviews, and documentation. The findings indicate that human resource management plays a crucial role in improving learning quality, particularly the vital function of educators (teachers) as facilitators in student success. Teachers are central to shaping the educational environment and fostering an atmosphere conducive to effective learning. Therefore, the availability and proper use of supporting facilities and infrastructure are essential in enhancing the overall educational process and ensuring the quality of learning. Furthermore, the integration of digital media has proven to be an effective tool for boosting the quality of learning for TKIT Al Mubarak students. The use of digital technology allows children to engage with educational content in a more interactive and enjoyable way. Digital media helps children learn about their surroundings and various concepts in an engaging manner, using diverse and dynamic programs that hold their attention. By incorporating these technologies into the classroom, students experience less boredom and greater enthusiasm for learning, leading to better educational outcomes. This study highlights the importance of both human resource management and technological integration in shaping a high-quality learning environment.